Modeling Impacts of Bark Beetle Infestations on Forest Visitor Experiences and Intended Displacement - Ingrid E Schneider; Arne Arnberger; Stuart P Cottrell; Eick von Ruschkowski (Forest Science, 2019)
Bark beetle outbreak impacts are occurring at reportedly unprecedented levels. Despite previous research on the aesthetic and economic impacts of terrestrial pest infestations, minimal visitor behavioral response research exists. As beetle infestation progresses, both tree appearance and landscape change can negatively impact visitation and visitor revenue. Given the multiple-use mandate of most forests, this lack of research is surprising. To meet this gap, this study simulated impacts of varied beetle outbreak levels, management approaches, and visitor characteristics on interference with forest visitors’ experience and intended displacement. Visitors at two forested US state park study sites, one with significant bark beetle impact and the other with much less, responded to onsite questionnaires with digitally calibrated photos depicting a variety of beetle-impacted forest scenarios. Up to 80 percent of visitors indicated forest scenarios with significant bark beetle impact would interfere with their experience, and 70 percent reported they would not visit or be displaced. Analyses revealed forest fore- and midground conditions with varying levels of impact significantly predicted both experience interference and displacement. The relative importance of social, biophysical, and managerial conditions differed between models. Results inform management and planning efforts as well as advance understanding of the biophysical and social factors influencing interference and intended displacement.